Barbarogenij, barbarsko in fašizem - Vrečko, Janez (Primerjalna književnost, 2012)
The expression "barbarically primitive artist-genius" that Srečko Kosovel used in his diaries of early 1924 followed the idea of the zenithist barbarogenius because he used it together with other zenithist syntagms and refers to broken-down European art and its revival with the help of the elementary and wild Balkans. This was a destructive poetic phase in Kosovel's life. However, from April 1925 onwards Kosovel accepted the concept of barbarianism outside the futuristic, zenithist, and other contexts; he thus renounced definitions of this concept based in poetry studies and nationalism, and began applying a distinctly political understanding of the concept of barbarianism connected with the threat that fascism posed to Slovenians living in the Littoral region.
Keywords: Kosovel, Srečko, 1904-1926; Micić, Ljubomir, 1895-1971; literature; književnost; politics; politika; literarna avantgarda; konstruktivizem; constructivism; zenitizem; barbarstvo; barbarogenij; fašizem